Differential MIR-21 Expression in Plasma From Mesenteric Versus Peripheral Veins. Issue 1 (January 2015) - Monzo, Mariano; Martínez-Rodenas, Francisco; Moreno, Isabel; Navarro, Alfons; Santasusagna, Sandra; Macias, Ismael; Muñoz, Carmen; Tejero, Rut; Hernández, Raquel; Kapritsou., Maria
<x xml:space="preserve">Abstract</x> Abstract Findings on the role of plasma miR-21 expression in colorectal cancer are contradictory. Before reaching a peripheral vein (PV), microRNAs released by the tumor are dispersed throughout the body. We hypothesized that blood drawn from the mesenteric vein (MV) near the site of the primary tumor could provide more homogeneous information than blood drawn from the PV. We have analyzed miR-21 expression in matched samples of tumor tissue, normal tissue, MV plasma, and PV plasma in 57 surgically resected patients with colon cancer and correlated our findings with clinical characteristics and disease-free survival (DFS). miR-21 expression was higher in MV than PV plasma (P = 0.014) and in tumor than in normal tissue (P < 0.001). Patients with high levels of miR-21 in MV plasma had shorter DFS (P = 0.05) than those with low levels, and those with high levels in both MV and PV plasma had shorter DFS than all other patients (P = 0.01). Our findings suggest that the primary tumor in colon cancer releases high concentrations of miR-21 in the MV but that these concentrations are later diluted in the circulatory system. MV expression of miR-21 may be a stronger prognostic marker than PV expression.